Exclusive Image Gallery on Human Spinal Cord Regeneration-Clinical Image-2 - Giselher Schalow (Imaging Journal of Clinical and Medical Sciences - Peertechz Publications, 2019)
Spinal cord (A) and dermatome segments (B-D). The segmental innervation of the skin in B is according to Hansen-Schliack and in C after Keegan and Garret. The overlap of dermatomes (D) is according to Foerster. Note the different location of the T1 dermatome in B and C. There is variation of the segmental skin innervation especially in the lower sacral range.